Association of Neutrophil Extracellular Traps with Fistula Healing in Patients with Complex Perianal Fistulizing Crohn's Disease. (2nd November 2022) - Cao, Dongxing; Qian, Keyu; Zhao, Ying; Hong, Jie; Chen, Haoyan; Wang, Xiaohui; Yang, Nailin; Zhang, Cheng; Cao, Jingkai; Jia, Keyu; Wu, Guangyu; Zhu, Mingming; et al.
Abstract: Background and Aims: Perianal fistulizing Crohn's disease [pfCD] is a disabling phenotype of Crohn's disease [CD] with suboptimal outcomes. We assessed neutrophil extracellular traps [NETs] in perianal fistulas and implicated their roles in pfCD healing. Methods: Patients with complex pfCD who developed preplaced seton drainage were recruited during the verified maintenance of remission in CD. Fistula tracts were sampled during definitive surgery plus seton removal. Patient demographics, CD classification, medication strategy and healing of pfCD were recorded. RNA sequencing was applied for transcriptomic profile analysis. NET components, including myeloperoxidase [MPO], neutrophil elastase [NE] and citrullinated histone H3 [CitH3], were identified using immunofluorescence. Serum infliximab [IFX], anti-IFX antibodies, and tissue levels of IFX, adalimumab [ADA], MPO and CitH3 were determined using enzyme-linked immunosorbent assays. Peptidyl arginine deiminase IV [PAD4], tumour necrosis factor [TNF]-α, and NE were detected using immunohistochemistry. Gene expression levels of PAD family members were assessed with quantitative PCR. Results: Twenty-one patients were included, 15 of whom adopted IFX as maintenance treatment. RNA-sequencing revealed differences in neutrophil associated pathways between unhealed and healed fistulas. NET components [MPO/NE/CitH3] were detectable in the fistulas and were parallel with the levels of PAD4. Eleven of 21 [52%] patients experienced complete healing of the pfCD 108 weeks post-operatively. Fistula NETs were significantly increased in patients with unhealed pfCD. Increased NETs were associated with abundant TNF-α production and the absence of IFX in fistulas. Conclusions: NETs exist in pfCD fistulas, which are associated with unhealed post-operative fistulas in pfCD, suggesting their prognostic roles in pfCD.